A Global Survey on Diseases and Pests in Oilseed Rape—Current Challenges and Innovative Strategies of Control - Zheng, Xiaorong; Koopmann, Birger; Ulber, Bernd; von Tiedemann, Andreas (Frontiers in Agronomy, 2020)
The introduction of high-yielding and hybrid cultivars and the opening of new markets in the food and feed sector have steadily increased rapeseed production since the 1980s in the main production regions, Canada, Europe, China, India and Australia. Since the 1990s, however, the average growth rate of yields has declined in Europe and Australia, which has been associated with a less effective control of biotic stresses. A global survey including the knowledge of 22 experts from ten countries revealed a total of 16 diseases, 37 insect pests, several species of nematodes and slugs currently affecting rapeseed production globally. A ranking of the top ten most important biotic stresses in the four global regions where Brassica napus is grown indicated an increase in several important stresses and distinct regional differences in the priority of prevailing diseases and pests. A stronger overlap exists among diseases, with Sclerotinia stem rot, Phoma stem canker and clubroot occurring in all the four global regions on the top ten list, while the range of prevailing insect pests was more diverse among the regions, with no top ten insect playing an equally important role worldwide. Management options are substantially broader in disease than in pest control, making the latter the larger challenge. Since common IPM tools such as crop rotation, soil management, resistant cultivars or biocontrol are ineffective or not available, insect control largely relies on insecticides. Increasing restrictions on insecticide use, particularly in Europe, and losses in insecticide efficacy threaten the profitability of oilseed rape production and its role as an important break crop in cereal dominated cropping systems. Since the survival time of insects in the absence of their main host is relatively short, a regional synchronization of cropping schemes resulting in one or more years without the crop could lead to a substantial disruption of regional insect populations. If rotation schemes were implemented on the landscape instead the farm level, by coordination among growers in zones covering the range distances of insect pests, an efficient and chemical low management strategy could be established and enable a more sustainable rapeseed production in the future.